2017
DOI: 10.1038/s41598-017-16938-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Atrial Fibrillation Recurrence after Catheter Ablation: Data from the German Ablation Registry

Abstract: Catheter ablation (CA) for atrial fibrillation (AF) has emerged as a widespread first or second line treatment option. However, up to 45% of patients (pts) show recurrence of AF within 12 month after CA. We present prospective multicenter registry data comparing characteristics of pts with and without recurrence of AF within the first year after CA. This study comprises all pts with complete follow-up one year after CA (1-y-FU; n = 3679). During 1y-FU in 1687 (45.9%) pts recurrence of AF occurred. The multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 28 publications
(40 reference statements)
6
100
4
1
Order By: Relevance
“…The prevalence of AF will surge in the next decade due to an aging population that is living longer with a high burden of comorbid conditions that are associated with AF . Catheter radiofrequency ablation (RFA) is one form of therapy widely used in clinical practice to treat symptomatic AF, but postprocedure recurrent AF occurs in 20% to 45% of patients . Direct current cardioversion (DCCV) interrupts AF and restores sinus rhythm, but has no durable effect.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AF will surge in the next decade due to an aging population that is living longer with a high burden of comorbid conditions that are associated with AF . Catheter radiofrequency ablation (RFA) is one form of therapy widely used in clinical practice to treat symptomatic AF, but postprocedure recurrent AF occurs in 20% to 45% of patients . Direct current cardioversion (DCCV) interrupts AF and restores sinus rhythm, but has no durable effect.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CTI block ablation is frequently performed in addition to left atrial (LA) ablation. The recurrence rate of AF was still significantly high after the first pulmonary vein isolation (PVI) by catheter ablation of AF, especially in patients with larger LA volume, prior non‐paroxysmal AF, in‐hospital AF relapse, impaired cardiac and renal function, and in female patients . A previous study reported that an LA volume greater than 145 mL was a predictor of atrial arrhythmia recurrence, even when adjusted for the effect of age, gender, body mass index, hypertension, and type of AF .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of risk factors on repeat ablation procedures has not been studied extensively. The above‐mentioned German registry found no differences in age, gender, or risk factors between patients with AF recurrence who did or did not undergo a repeat procedure . It has to be noted, however, that only 47.5% of patients with AF recurrence underwent a repeat procedure, which may be related to the short duration of the AF episodes that was defined as recurrence.…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between risk factors and AF recurrence has been studied before in a German multicenter registry of 3679 patients with 1‐year follow‐up after ablation . Recurrence rate was 45.9% and female sex (OR 1.27; 95% CI 1.11–1.46), valvular heart disease (OR 1.29; 95% CI 1.02–1.63), heart failure (OR 1.58; 95% CI 1.36‐1.84), and renal failure (OR 3.35; CI 1.08–10.41) significantly predicted AF recurrence during 1‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%